Régénération naturelle à faible coût dans le cadre de l’aménagement forestier en zones tropicales sèches en Afrique - Ronald Bellefontaine (VertigO)
In several dryland African countries, forest management process is expansive, even when it is simplified. To find out the allowable cut, forest management inventories should be conducted, taking into account not only the natural regeneration by seeds but also the sprout by various vegetative means. As of today, only two categories, the stump sprouts and the “seedlings”, are accounted for. For numerous species, rejuvenation through terrestrial layering and root suckering is not enough considered by forest managers and /or by rural communities in charge of forest management. In countries with very low forest cover, we have to manage the open woodlands and also the trees outside forest, which are used for various purposes by farmers and breeders of semi-arid and arid tropical zones. In some cases, open woodlands and trees outside forest have an important potential for root suckering or terrestrial layering. Thanks to the natural processes, some species (more than 360) manage to survive in a threatened environment. Sometimes they may colonize the ecosystem during the rainy season by producing adventive stems from the root system through suckering and from aerial system (branch or stem) for the layering. In some cases, reiterates appear on trunks  blown down by the wind and take roots.Several factors may have an effect on the ability to produce sprouts from the basis of the stem (basal sprout, root crown), from the branches (layer, rhizome, runner) or from roots (sucker). In most cases, a stress is necessary (ploughing, fire, illness, cyclone, drought, cold, etc). For the trees growing just at the border of their altitudinal or longitudinal natural area, the seedling survival becomes a problem, and as a consequence certain types of sprouts and terrestrial layering may become more frequent. This process should be developed especially in poorest developing countries for trees outside forest regeneration in or around fields, as well as for enrichment and forest management.